Early Anesthesia Exposure and the Effect on Visual Acuity, Refractive Error, and Retinal Nerve Fiber Layer Thickness of Young Adults - Yazar, S.; Hewitt, A.; Forward, H.; Jacques, Angela; Ing, C.; von Ungern-Sternberg, B.; Mackey, D. (Mosby, Inc., 2016)
OBJECTIVE: To investigate whether being anesthesia administered at least once in early life influenced 3 main proxies of visual function: visual acuity, refractive error, and optic nerve health in young adulthood. STUDY DESIGN: At age 20 years, participants of the Western Australian Pregnancy Cohort Study had comprehensive ocular examinations including visual acuity, postcycloplegic refraction, and multiple scans of the optic disc. We identified individuals who had at least 1 procedure requiring anesthesia during the first 3 years of life (between 1990 and 1994) and compared their visual outcomes with nonexposed individuals. We excluded 40 participants with strabismus or other ophthalmic disease or surgery and 136 with non-European background. RESULTS: Of 834 participants, 15.2% (n = 127) were exposed to anesthesia at least once before age 3 years. In both exposed and nonexposed groups, median visual acuity (measured using the logarithm of the minimum angle of resolution [LogMAR] chart) was -0.06 LogMAR in the right eye and -0.08 LogMAR in the left eye (P > .05). Median spherical equivalent refractive error was +0.44 diopters (IQR -0.25, +0.63) and +0.31 diopters (IQR -0.38, +0.63) in the exposed and nonexposed group, respectively (P = .126). No difference was detected in mean global retinal nerve fiber layer thickness of the 2 groups (100.7 vs 100.1 mum, P = .830). CONCLUSIONS: We were unable to demonstrate an association of exposure to anesthesia as a child with reduced visual acuity or increased myopia or thinning of retinal nerve fiber layer. These findings support the view that anesthesia is unlikely to impair visual development, but further work is needed to establish whether more subtle defects are present and repeated exposures have any effects.